PENGEMBANGAN USAHA BATIK SOLO DALAM MENGHADAPI PASAR GLOBAL - Pujiani, Dewi (Universitas Slamet Riyadi, 2015)
Batik business development in the face of global market is very important to be prepared with mature and should be based on with seriousness in making the batik business as a reliable business. An important factor in global markets, namely the United Kingdom language unity in doing business, especially in business batik exported abroad. The company batik joined his global marketing staple the two variables should consider in order to take effective decisions. Globalization cause limits business between countries invisible. Foreign designers attracted by the results of Indonesia's culture, is about batik. Therefore, the domestic batik want to preserve to be shown on world. The benefits of developing a solo batik business was able to preserve the craft batik solo that can be marketed in global marketing. The purpose of this article is that of batik solo to preserve it in both national and international level. Keywords: Global market, batik, exported, business